The Effect of Employee Satisfaction on Employee Performance with Employee Loyalty and Employee Engagement as Mediating Variables in Manufacturing Sector Employees in Jabodetabek - Adhihusada, Christophorus Kevin; Gunawan, Andreas Wahyu (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the effect of Employee Satisfaction on Employee Performance, mediated by Employee Loyalty and Employee Engagement, among manufacturing sector employees in Jakarta. Data were collected from 266 respondents using purposive sampling. Descriptive statistics and hypothesis testing were conducted using AMOS software version 26. The results indicate that Employee Satisfaction positively influences Employee Loyalty, Employee Engagement, and Employee Performance. Additionally, Employee Loyalty and Employee Engagement both positively influence Employee Performance. Regarding indirect effects, Employee Loyalty partially mediates the relationship between Employee Satisfaction and Employee Performance, while Employee Engagement also partially mediates this effect. The managerial implications suggest that management can improve employee performance by providing training to meet employee needs, ensuring employees apply what they have learned at work, fostering ongoing communication and involvement, and motivating employees to feel confident in their tasks.